The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10484-007-9034-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Effects of Breathing Instructions for Stress Management

Abstract: Stressed and tense individuals often are recommended to change the way they breathe. However, psychophysiological effects of breathing instructions on respiration are rarely measured. We tested the immediate effects of short and simple breathing instructions in 13 people seeking treatment for panic disorder, 15 people complaining of daily tension, and 15 controls. Participants underwent a 3-hour laboratory session during which instructions to direct attention to breathing and anti-hyperventilation instructions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 29 publications
2
46
0
Order By: Relevance
“…Specifically, HRV increases when short inspiration is followed by long expiration – which has implications for tasks that require speech production (Cysarz et al, 2004) and many forms of meditation, for instance. Even monitoring spontaneous breathing has been found to reduce respiratory variability (Cysarz and Büssing, 2005; Conrad et al, 2007). HR driven cardiorespiratory coupling also appears to increase when HRV is higher (Galletly and Larsen, 2001).…”
Section: Caveats and Considerationsmentioning
confidence: 99%
“…Specifically, HRV increases when short inspiration is followed by long expiration – which has implications for tasks that require speech production (Cysarz et al, 2004) and many forms of meditation, for instance. Even monitoring spontaneous breathing has been found to reduce respiratory variability (Cysarz and Büssing, 2005; Conrad et al, 2007). HR driven cardiorespiratory coupling also appears to increase when HRV is higher (Galletly and Larsen, 2001).…”
Section: Caveats and Considerationsmentioning
confidence: 99%
“…These benefits can be explained by the fact that deep and slow breathing exercises contrast the effects of fast and shallow chest breathing, which is a common automatic habit, e.g., in patients with anxiety disorders (Hazlett-Stevens, 2008). In general, hyperventilation can lead to physical sensations resembling anxiety (HazlettStevens, 2008) and symptoms typical of panic attacks (Conrad et al, 2007). Furthermore, several medical studies have reported that breathing exercises can also have positive effects on the circulatory system, by helping to lower blood pressure (Grossman et al, 2001;Joseph et al, 2005;Radaelli et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Conscious control of breathing, such as during breathing exercise, provides a mechanism for conscious control of autonomous nervous system and-to some degree-a conscious control of involuntary body processes. Today, breathing exercises are being used as a complementary treatment of hypertension [17][18][19][20][21][22][23][24][25], asthma [26][27][28][29][30], sleep disorders [31,32], and stress/anxiety-related disorders [33][34][35][36][37][38]. Technical solutions that allow detection of breathing frequency do already exist [31,[39][40][41][42][43][44][45][46], but they are not easily integrated with a computer to enable interactive pacedbreathing exercises.…”
Section: Introductionmentioning
confidence: 99%